Numerical Study for Identifying Damage in Open Hole Composites with Embedded FBG Sensors and Its Application to the Experimental Results - MURAI, Kazue; YASHIRO, Shigeki; OKABE, Tomonaga; TAKEDA, Nobuo (Journal of the Japan Society for Composite Materials, 2006)
This study proposes two new approaches for estimating the damage patterns in a holed CFRP cross-ply laminate using an embedded fiber Bragg grating (FBG) sensor. It was experimentally confirmed that the reflection spectrum from the embedded FBG sensor drastically changed as the damage near the hole, i.e. splits, transverse cracks and delamination, extended. The damage patterns were predicted using forward analysis (a damage analysis and an optical analysis) with strain estimation and the proposed damage-identification method as well as the forward analysis only. The forward analysis with the strain estimation then to be yielding the best prediction from the viewpoint of the accuracy in estimating the damage pattern and the computational efficiency. Furthermore, the proposed damage identification achieved a significant reduction in the computational time and the equivalent accuracy compared to the conventional identification procedure, adopting the damage pattern obtained by the damage analysis as the initial estimation.